The effect of germination and food processing on the concentration and activity of bioactive compounds in Australian Sweet Lupin - Rumiyati (Curtin University, 2010)
Lupin is a grain legume which is high in protein and fibre, but low in fat and starch. Lupin also contains bioactive compounds such as phenolic compounds. Many studies have shown that a diet containing lupin has health benefits including reducing a number of risk factors associated with metabolic syndrome. However, studies examining the effect of germination of Australian Sweet Lupin (ASL) on its macronutrient, bioactive compounds and bioactivity are limited. Consequently the aim of the present study was to investigate the changes in the macronutrient composition and concentration of bioactive compounds in ASL during germination and how these changes were associated with in vitro bioactivity. The stability of bioactive compounds and their in vitro bioactivity was also investigated in muffins incorporated with germinated ASL flour (before and after baking).In the present study, the macronutrient composition (protein, crude fibre and fat) and bioactive compound concentration (phenolic compounds and phytosterols) of ASL following germination at 25°C and 90-95% relative humidity for 9 days were determined. Total phenolic compounds (TPC) were extracted from germinated ASL flour using methanol and aqueous solvents and the concentration was determined using Folin-Ciocalteu reagent. Phytosterols in oil extracts were analyzed using gas-liquid chromatography. The radical scavenging activities toward 2, 2-diphenyl-1-picrylhydrazyl (DPPH) of the methanolic and oil extracts were also determined. Bioactivity related to bile acid binding in vitro of germinated ASL flour was also assessed. The changes in the pattern of ASL protein during germination were analysed using sodium dodecyl sulphate-polyachrilamide gel electrophoresis (SDS-PAGE) and matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS). The changes in the protein pattern were then compared with the result of Angiotensine I Converting Enzyme (ACE) inhibitory activity assay of the protein. Total protein extracts of germinated ASL flour were then fractionated into the protein isolate fraction and the soluble fraction. Both fractions were characterized for their activities including antioxidant activity, bile acid binding ability and ACE-inhibitory activity. ASL flour after germination for 7 days was chosen to be incorporated into muffin formulation at substitution levels of 2 - 8% of dried muffin weight. Physical characteristics of muffins including height, diameter, colour and texture (hardness, cohesiveness, springiness and chewiness) were measured instrumentally. Stability of the bioactive compounds and the antiradical activity of the incorporated muffins before and after baking were also investigated.Germination at day 9 resulted in significant increase in protein and crude fibre contents of ASL by 38% and 456% (db), respectively, and resulted in a substantial reduction in the lipid content of ASL by 71%. Germination also increased the concentration of total phenolic compounds in methanolic extracts of germinated ASL flours by about 700% compared to ASL flour of ungerminated seeds. The increased concentration of phenolic compounds was found to be associated with significant increased radical scavenging activity of the extracts. Concentration of the total phytosterols which was extracted from germinated ASL flour were also increased by 3 fold. The significant increase in phytosterol content in the oil may be associated with increasing in the antiradical activity of the oil. The main phytosterols in the oil extracted from germinated ASL flour are β-sitosterol (62%), campesterol (30%) and stigmasterol (8%). In the protein fraction, the high molecular weight proteins of ASL were not present following germination for 9 days. The change in the protein profile may be associated with the higher ACE inhibitory activity (antihypertensive in vitro) of germinated ASL flour. The protein isolated from germinated ASL flour had better antioxidant activity, while its soluble fraction was better in ACE inhibitory activity and bile acid binding property. The bile acid binding ability of germinated ASL flour had higher bile acid binding ability in vitro than ungerminated ASL flour.Furthermore, incorporation of germinated ASL flour up to 8% (db of muffins) into the muffin formulation influenced moisture, height, diameter, colour, hardness and cohesiveness of the muffins. This incorporation increased the total phenolic compounds, phytosterols content and antiradical activity of the muffins. The baking process at 190°C for 25 min did not substantially reduce the concentration of total phenolic compounds, phytosterols and the antiradical activity of the muffins.The present study found that germination led to an increase in protein and fibre contents and concentration of bioactive compounds of ASL. Germination also increased in vitro antioxidant activity, ACE inhibitory activity and bile acid binding ability of ASL.